Design of the randomized, Phase III, QUAZAR AML Maintenance trial of CC-486 (oral azacitidine) maintenance therapy in acute myeloid leukemia. (February 2016) - Roboz, Gail J; Montesinos, Pau; Selleslag, Dominik; Wei, Andrew; Jang, Jun-Ho; Falantes, Jose; Voso, Maria T; Sayar, Hamid; Porkka, Kimmo; Marlton, Paula; Almeida, Antonio; Mohan, Sanjay; et al.
Older patients with acute myeloid leukemia (AML) have worse rates of complete remission and shorter overall survival than younger patients. The epigenetic modifier CC-486 is an oral formulation of azacitidine with promising clinical activity in patients with AML in Phase I studies. The Phase III, randomized, double-blind, placebo-controlled QUAZAR AML Maintenance trial (CC-486-AML-001) examines CC-486 maintenance therapy (300 mg/day for 14 days of 28-day treatment cycles) for patients aged ≥55 years with AML in first complete remission. The primary end point is overall survival. Secondary end points include relapse-free survival, safety, health-related quality of life and healthcare resource utilization. This trial will investigate whether CC-486 maintenance can prolong remission and improve survival for older patients with AML.